2021
DOI: 10.1007/s00062-020-00989-w
|View full text |Cite
|
Sign up to set email alerts
|

Acute Endovascular Stroke Treatment in Germany in 2019

Abstract: Purpose Since the incidental discovery and systematic introduction of mechanical endovascular stroke treatment in 2015 there are few reports about the real-life situation in daily clinical practice. The aim of this study was to evaluate the mechanical thrombectomy data documented in the quality assurance database of the German Society for Interventional Radiology and Minimally Invasive Therapy (DeGIR) and the German Society of Neuroradiology (DGNR) in 2019. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 17 publications
1
13
1
2
Order By: Relevance
“…Another important factor potentially negatively affecting the clinical outcome of infectious patients treated with MT due to LVO is the significant delay in performing thrombectomy. The median time interval from symptom onset to groin puncture in our study was higher than findings of the German Stroke Registry in 2019 (median 220 min vs 160 min) 27. Additionally, the time interval from onset to groin puncture presented as an independent predictor for an unfavorable outcome in our multivariate analysis.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Another important factor potentially negatively affecting the clinical outcome of infectious patients treated with MT due to LVO is the significant delay in performing thrombectomy. The median time interval from symptom onset to groin puncture in our study was higher than findings of the German Stroke Registry in 2019 (median 220 min vs 160 min) 27. Additionally, the time interval from onset to groin puncture presented as an independent predictor for an unfavorable outcome in our multivariate analysis.…”
Section: Discussioncontrasting
confidence: 73%
“…The median time interval from symptom onset to groin puncture in our study was higher than findings of the German Stroke Registry in 2019 (median 220 min vs 160 min). 27 Additionally, the time interval from onset to groin puncture presented as an independent predictor for an unfavorable outcome in our multivariate analysis. Multiple studies have shown declines in the volumes of MT, IVT and stroke hospitalizations over the pandemic with delays in hospital arrival times and treatment workflow.…”
Section: Discussionmentioning
confidence: 79%
“…Registries and quality standards: Two data models from the association of German stroke registries (ADSR) are considered, one regarding acute care for stroke patients in hospitals and one regarding thrombectomy and lysis therapy after stroke [ 9 , 22 ]. Moreover, a registry from Austria was included in the analysis [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…We realize that there are many patients who have been failed by the present system, but since they are not reported, we cannot see the scale of the need that is unmet [ 39 , 41 , 42 ]. Given the number of mechanical thrombectomy procedures performed in other healthcare systems in the world, we can only estimate that we provide good services to less than half of the eligible patients [ 13 17 ]. In 2020, approximately 90,000 patients diagnosed with acute stroke were hospitalized in Poland, with roughly 75,000 identified as ischemic.…”
Section: Mt Pilot Program In Polandmentioning
confidence: 99%
“…Among those, 33,000 cases were diagnosed to be LVO strokes, of which 11,580 were thrombectomy-eligible (the sum of patients presenting with LVO within 6 h from onset and those presenting later with favorable perfusion criteria), which makes 13% of all ischemic strokes [ 43 ]. Germany with its staggering 150 MT-center-strong network treats 7.2% of ischemic strokes invasively [ 13 ], and the Czech Republic even more (7.5–8.1%) [ 16 ]. France, with almost twice as many MT centers at its disposal (2018) as Poland today, decided to implement considerable changes to improve access to endovascular treatment.…”
Section: Mt Pilot Program In Polandmentioning
confidence: 99%